Kooperation und Geheimnisschutz bei Beweisschwierigkeiten im Zivilprozess Möglichkeiten der geschützten Verwertung von Unternehmensgeheimnissen im Spannungsfeld von rechtlichem Gehör, effektivem Rechtsschutz und prozessualen Kooperationspflichten - Rassi, Jürgen C.T (Jan Sramek Verlag, 2020)
The work shows the connection between the duties of cooperation and the interest in secrecy. The concept of trade secrets is examined in more detail and discussed as the limit of the civil procedural obligation to cooperate. The procedural protection of trade secrets is incomplete because it is limited to parts of the evidence procedure and is partly characterised by a rigid weighing of interests.